Effect of different biomass concentration on biological pretreatment to chemical pulping process - Nor Hanimah, Hamidi (2006)
Biological pulping (biological pretreatment) has been an area where it has been stated that there is a need for a “breakthrough technology”. Biological pulping is the treatment of lignocellulosic materials with oxidative lignin-degrading microorganism enzymes prior to pulping process. The aim of this study is to determine the effect of different biomass concentration on biological pretreatment to chemical pulping process. By using three different concentrations of biomass (B1, B2 and B3) banana stem waste will be treated through biological pretreatment. Treated banana stem waste will be proceeding to chemical pulping process. Untreated banana stem waste as control will also experienced chemical pulping process through the same conditions. Compositions of lignin, cellulose and glucose have been analyzed before and after biological pretreatment and after chemical pulping process by using different method and procedures. From this study, the higher biomass concentration gives the higher percentage of lignin degradation. Biological pretreatment shows the positive response to chemical pulping process where banana stem waste that have been treat in biological pretreatment process degrade the lignin in the short period of time in chemical pulping process where it takes only 30 minutes to degrade the lignin compare to 2 hours chemical pulping processes that have been stated in the literature review. This result shows that biological pretreatment helps to reduce time and energy consumption in chemical pulping process.